2011
DOI: 10.4236/jep.2011.23035
|View full text |Cite
|
Sign up to set email alerts
|

On the Current and Restoration Conditions of the Southern Iraqi Marshes: Application of the CCME WQI on East Hammar Marsh

Abstract: Water quality of the East Hammar marsh after restoration was assessed by using the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI).The model was applied in two approaches based on the historical data and the CCME aquatic life guidelines as objectives. Variables included in the index calculation were Water Temperature, Dissolved Oxygen, Salinity, pH value, Total Nitrogen, Ammonia, Nitrate, Phosphorus and Sodium. The CCME WQI analysis in both approaches reflected that water qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The findings are consistent with other studies [e.g.,3] that noted that some water chemistry parameters of Al-Hammar Marsh, when compared with historical surveys completed before drainage [ 36 , 37 , 38 , 39 ], revealed high increases. This considerable increase in ion concentrations is probably related to a rise in salinity in the main feeder of the marsh (e.g., the Euphrates River) and to increased flux into the water column of ions concentrated in the soil after more than a decade of drainage and evaporation [10] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are consistent with other studies [e.g.,3] that noted that some water chemistry parameters of Al-Hammar Marsh, when compared with historical surveys completed before drainage [ 36 , 37 , 38 , 39 ], revealed high increases. This considerable increase in ion concentrations is probably related to a rise in salinity in the main feeder of the marsh (e.g., the Euphrates River) and to increased flux into the water column of ions concentrated in the soil after more than a decade of drainage and evaporation [10] .…”
Section: Resultsmentioning
confidence: 99%
“…Al-Hammar Marsh, one of the three biggest marshes in Iraq, is situated to the south of the Euphrates River (30 45'–30° 59' N, 46° 25'–47° 15' E) and has an area ranging from 2800 km 2 of contiguous permanent marsh to 4500 km 2 during flooding periods. The marsh that is fed mainly by the Euphrates River, Tigris River, the Central Marshes, and groundwater recharge drains ultimately into the Shatt Al-Arab River, which empties into the Arabian Gulf [10] . Al-Hammar Marsh had been desiccated for more than a decade; however, the marsh was restored to around half of its original size in 2005 after a policy was initiated to restore the marshes in 2003 [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers turned to evaluate the water quality of Al-Hammar Marsh after restoration by using the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) for a different period [20] assessed water quality of the East Hammar for 2005-2006. The results reflect that the marsh area is still far from the current guideline criteria and, too far from restoration, while [21]evaluated the water quality in Al-Hamedy Station, located in the middle of the marsh and related to the Al-Basra Governorate from 2011 to 2015, the Arithmetic Weighted Index was employed to determine the (WQI in the Al-Hammar Marsh, the results showed that the marsh water was brackish because of the high concentration of totally dissolved solids flowing in from the estuaries of the feeding channels coming from the river Euphrates, as well as from the tidal phenomenon via river Shatt Al-Arab.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been focus on describe water quality and the fish assemblages in the southern marshes since inundation in 2003 (ARID, 2006;Hussain et al, 2009;Mohamed et al, 2008Mohamed et al, , 2012Mohamed et al, , 2014. Some works have been carried out attempting to evaluate water quality change as result of environmental alteration in the marshes by using Water Quality Index, WQI or water characteristics (Al-Saboonchi et al, 2011;Al-Kenzawi et al, 2011) or fish structure changes in the marshes by applying the Index of Biotic Integrity, IBI (Al-Shamary, 2008;Mohamed and Hussain 2012a;Mohamed 2014a, b).…”
Section: Introductionmentioning
confidence: 99%